Caspase-cleaved Tau Expression Induces Mitochondrial Dysfunction in Immortalized Cortical Neurons: IMPLICATIONS FOR THE PATHOGENESIS OF ALZHEIMER DISEASE - Quintanilla, Rodrigo A. (American Society for Biochemistry and Molecular Biology, 2009)
In Alzheimer disease (AD) mitochondrial abnormalities occur early in the pathogenic process and likely play a significant role in disease progression. Tau is a microtubule-associated protein that is abnormally processed in AD, and a connection between tau pathology and mitochondrial impairment has been proposed. However, few studies have examined the relationship between pathological forms of tau and mitochondrial dysfunction. We recently demonstrated that inducible expression of tau truncated at Asp-421 to mimic caspase cleavage (T4C3) was toxic to immortalized cortical neurons compared with a full-length tau isoform (T4). In this study we investigated the effects of T4C3 on mitochondrial function. Expression of T4C3 induced mitochondrial fragmentation and elevated oxidative stress levels in comparison with T4-expressing cells. Thapsigargin treatment of T4 or T4C3 cells, which causes an increase in intracellular calcium levels, resulted in a significant decrease in mitochondrial potential and loss of mitochondrial membrane integrity in T4C3 cells when compared with cells expressing T4. The mitochondrial fragmentation and mitochondrial membrane damage were ameliorated in T4C3 cells by pretreatment with cyclosporine A or FK506, implicating the calcium-dependent phosphatase calcineurin in these pathogenic events. Increased calcineurin activity has been reported in AD brain, and thus, inhibition of this phosphatase may provide a therapeutic target for the treatment of AD.